On Topological Properties Involving Semi-Open Sets - Rulete, Ricky; Canoy, Sergio Jr. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
In this paper, the concept of s-connectedness will be introduced. Some results concerning the relationship between connectedness and s-connectedness will be given. In particular, it is shown that connectedness is weaker than s-connectedness. Characterizations of s-connectedness are also obtained.